2010
DOI: 10.1002/jso.21796
|View full text |Cite
|
Sign up to set email alerts
|

Impact of blood transfusion on early outcome of liver resection for colorectal hepatic metastases

Abstract: These clinical findings suggest that although several significant factors do not seem to influence the short-term outcome of surgery, it is important to be aware of the deleterious effects of the type of resection performed and the presence of portal fibrosis on blood loss during partial liver resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 15 publications
4
31
0
Order By: Relevance
“…In the present study, a significant increase in fluid replacement was observed in patients receiving neo-adjuvant chemotherapy in the matched population. As also observed in the present multivariate analysis, higher intra-operative blood loss is an established risk factor for post-operative morbidity and mortality [15,30,31], so it is reasonable to suppose a role for this factor in determining the increase of morbidity observed in treated subjects of the present study population. Neo-adjuvant chemotherapy can lead to increased intraoperative blood loss that, in turn, could lead to a relative increase in morbidity.…”
Section: Discussionsupporting
confidence: 71%
“…In the present study, a significant increase in fluid replacement was observed in patients receiving neo-adjuvant chemotherapy in the matched population. As also observed in the present multivariate analysis, higher intra-operative blood loss is an established risk factor for post-operative morbidity and mortality [15,30,31], so it is reasonable to suppose a role for this factor in determining the increase of morbidity observed in treated subjects of the present study population. Neo-adjuvant chemotherapy can lead to increased intraoperative blood loss that, in turn, could lead to a relative increase in morbidity.…”
Section: Discussionsupporting
confidence: 71%
“…All identified studies were observational design studies involving a total of 10621 patients. Seven studies were from USA [5, 7, 9, 16, 21, 22, 24], four from Italy [4, 8, 12, 13], three from Japan [3, 14, 18], two from UK [11, 25], two from Germany [20, 23], one from Sweden [2], one from France [6], one from Spain [10], one from Brazil [15], one from China [17], one from Canada [19], and one from the Netherlands [26]. The blood product transfusion rate was highly variable across studies ranging from 13.5% to 91.5%.…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of RBCT impact on morbidity pertaining specifically to liver resection remains limited. All studies rely on retrospective data from single centres (24,38,39). The largest such study reported increased morbidity, mortality, and LOS in transfused patients, but dates back to the 1980s and 1990s (24).…”
Section: Discussionmentioning
confidence: 99%
“…The largest such study reported increased morbidity, mortality, and LOS in transfused patients, but dates back to the 1980s and 1990s (24). Two other studies used contemporary data and revealed similar associations between RBCT and morbidity, but were of limited sample size (38,39). The current study represents a unique addition to the literature as it takes into account the uniqueness of liver resection, uses contemporary data, and is the first multi-institutional appraisal of the relationship between RBCT and short-term post-operative outcomes.…”
Section: Discussionmentioning
confidence: 99%